Heart rate dynamics and asymmetry during sympathetic activity stimulation and post-stimulation recovery in ski mountaineers—a pilot exploratory study - Gąsior, Jakub S.; Gąsienica-Józkowy, Maciej; Młyńczak, Marcel; Rosoł, Maciej; Makuch, Robert; Baranowski, Rafał; Werner, Bożena (Frontiers in Sports and Active Living, 2024)
There is lack of studies on non-linear heart rate (HR) variability in athletes. We aimed to assess usefulness of short-term HR dynamics and asymmetry parameters to evaluate the neural modulation of cardiac activity based on non-stationary RR interval series by study their changes during sympathetic nervous system activity stimulation (isometric hand-grip test) and post-stimulation recovery in professional ski mountaineers. Correlation between changes in parameters and respiratory rate (RespRate) but also career duration was analyzed. Short-term (5 min) and ultra-shortterm (1 min) rate of patterns with no variations (0V), number of acceleration runs of the length 1 (AR1) and short-term Porta's Index were larger, whereas Guzik's Index (GI) were smaller during sympathetic stimulation compared to rest. GI increased and number of AR1 decreased during recovery. Greater increase in GI and RMSSD were associated with higher decrease in RespRate during recovery. Higher increase in RespRate from rest to short-term sympathetic stimulation was associated with greater increases in 0V (Max-min method) and AR1 but also with greater decreases in decelerations of short-term variance and accelerations and decelerations of long-term variance. Higher increases in 0V (Max-min method) and number of AR1 during sympathetic stimulation were associated with shorter career duration. Bigger decreases in these parameters during recovery were associated with longer career. Changes in measures of HR dynamics and asymmetry, calculated based on short-term non-stationary RRi time series induced by sympathetic stimulation and poststimulation recovery, reflected sympathovagal shift and were associated with conditions-related RespRate alterations and career duration in athletes who practice ski mountaineering.